For all your questions, big or small, IDNLearn.com has the answers you need. Explore a wide array of topics and find reliable answers from our experienced community members.
Sagot :
Answer:
[tex]a. \(y = \frac{2}{3}x + \frac{11}{3}\)
\\ \\ \\
b. \(y = \frac{3}{2}x + 5\)[/tex]
solution ⤵️⤵️
[tex]a. For \: line \: A, \: the \: equation \: is \: already \: in slope \: -intercept \: form, \: which \: is \: \: \(y = \frac{2}{3}x + \frac{11}{3}\). \: This \: means that \: the \: slope \: of \: the line \: is \: \: \(\frac{2}{3}\) \: and \: the \: y-intercept \: is \: \(\frac{11}{3}\).
\\ \\ \\
b. To \: find \: the \: point-slope \: equation \: for \: line \: B, \: we \: start \: with \: the \: equation \: \: \(y + 1 = \frac{3}{2}(x + 4)\). \: By \: expanding \: and \: simplifying, \: we \: get \: \: \(y = \frac{3}{2}x + 5\). \: This shows \: that \: the \: slope \: of \: line \: B \: is \: \: \(\frac{3}{2}\) \: and \: it \: passes through \: the \: point (-4, -1).[/tex]
swipe right.
Answer:
Second Option:
[tex]y = -\dfrac{2}{3}x +\dfrac{11}{3}; \:\: y - 1 = \dfrac{3}{2}(x - 4)[/tex]
Step-by-step explanation:
We have two lines on the graph labeled Line A and Line B
Part (a) : Slope intercept form for Line A
The equation of a line in slope-intercept form is
y = mx + b
where
m is the slope - rate of change of y w.r.t x
b is the y-intercept - the value of y at x = 0
To determine slope of a line:
- Take two points lying on the line
- Find the difference in their y-coordinate values (also called rise )
- Find the difference in the corresponding x-coordinate values(also called run)
- Divide rise by run:
Slope = Rise/Run
Mathematically if the two points on a line are labeled (x1, y1) and (x2, y2) then the slope is given by the formula
[tex]m = \dfrac{y2 - y1}{x2-x1}[/tex]
The y-intercept can be computing by taking any point on the line and plugging in (x, y) values and solving for b
Equation For Line A in slope- intercept form
Two convenient points on Line A are (1, 3) and (4, 1)
[tex]m = \dfrac{1 - 3}{4 - 1} = - \dfrac{2}{3}[/tex]
Therefore
Equation of Line A:
[tex]y = -\dfrac{2}{3}x + b[/tex]
Take point (1, 3) and substitute in the above equation:
[tex]3 = -\dfrac{2}{3}\cdot 1 + b\\\\3 = -\dfrac{2}{3}\cdot 1 + b\\\\3 + \dfrac{2}{3} = b\\\\\dfrac{9}{3} + \dfrac{2}{3} = b\\\\\dfrac{11}{3} = b\\\\or\\b = \dfrac{11}{3}[/tex]
Therefore equation Line A is
[tex]y = -\dfrac{2}{3}x +\dfrac{11}{3}[/tex]
We see that this eliminates the first choice which has 2/3 as the slope
Part (b): Equation of Line B in point-slope form
The point slope equation for a line is
y - y1 = m(x - x1)
where
m is the slope
(x1, y1) is any point on the line
We can calculate the slope of Line B as we did for Line A:
Take points(0, -5) and (4, 1) which lie on Line B
[tex]\text{Slope $ m = \dfrac{1 - - 5}{4 - 0} = \dfrac{6}{4} = \dfrac{3}{2}$}[/tex]
So equation of Line B in point slope form
[tex](y - y1) = \dfrac{3}{2}(x - x1)[/tex]
Take point (x1, y1)= (4, 1). This is a convenient point since the coordinates are positive and less confusing to work with
Equation becomes
[tex]y - 1 = \dfrac{3}{2}(x - 4)[/tex]
Therefore the correct choice which corresponds to both equations the second option
[tex]y = -\dfrac{2}{3}x +\dfrac{11}{3}; \:\: y - 1 = \dfrac{3}{2}(x - 4)[/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Your questions deserve accurate answers. Thank you for visiting IDNLearn.com, and see you again for more solutions.